Analisis Kinerja Saham pada Industri Makanan dan Minuman Di Bursa Efek Indonesia dengan Model Sharpe Periode 2013-2017 - Florianus Ardy Bernando (Science of Management and Students Research Journal (SMS), 2020)
The Background of this research is to know magnitude return, to know risk magnitude and to know performance asset and to know performance rating from stock at the food and baverage industry. This research is disgnated to the food and baverage Industry, that is PT. Indofood Sukses Makmur Ltd. (INDF), PT. Multi Bintang Indonesia (MLBI), and PT. Indofood CBP Sukses Makmur Ltd. (ICBP) listed on the indonesian Stock Exchange period 2013-2017.The tool analysis which used is actual return, standart deviation and indeks sharpe or Reward to Variability (RVAR), the next from result performance or value RVAR will stratified start the rating highest until the rating lowest. Research result obtained during period 2013-2017 the highest return was owned by PT. Indofood CBP Sukses Makmur Ltd (ICBP) charge of 0.0257 or 2.57 percent and lowest return was owned by PT. Indofood Sukses Makmur Ltd. (INDF) charge of 0.0066 or 0.66 percent. The highest Risk asset was owned by PT. Indofood CBP Sukses Makmur Ltd (ICBP) charge of 0.1466 or 14.66 percent and the low risk asset was owned by PT. Indofood Sukses Makmur Ltd (INDF) charge of 0.0658 or 6.58 percent. With an average during five years value RVAR all its worth negative to three company. It can be conclude perfomance of stock was not good.